Competitiveness assessment of the Philippine Retirement Authority's program in international retirement migration - Aubrey D. Tabuga; Francis Mark A. Quimba; Madeleine Louise S. Bai\~no; Danika Astilla-Magoncia; Anna Rita P. Vargas; Mark Gerald C. Ruiz (Philippine Institute for Development Studies (PIDS), 2024)
The Philippines has introduced initiatives to attract retirement migrants, including visa and residence permit programs and various incentives. Central to these efforts is the Special Resident Retiree's Visa (SRRV), managed by the Philippine Retirement Authority (PRA). The SRRV offers a non-immigrant visa to foreign nationals and former Filipinos, allowing indefinite stay and multiple entries. This paper, one of a three-part research paper series, aims to assess the competitiveness of PRA's retirement program compared to neighboring countries, profile prospective retirees, and identify ways to enhance PRA's program effectiveness. Using a mixedmethods approach, the study integrates quantitative and qualitative analyses, including competitor SWOT analysis, customer feedback, and value-chain evaluation. It examines literature on retirement migration trends and conducts key informant interviews with retirees and PRAaffiliated entities. Findings reveal that while the Philippines' SRRV program is attractive due to lower financial requirements and indefinite stay privileges, it lags behind countries like Thailand and Malaysia in attracting retirees. Issues such as visa processing delays, unclear requirements, and limited post-visa services detract from its appeal. Additionally, retirees are often younger than expected, and most come from high-income backgrounds. To improve, the PRA must address processing delays, enhance after-sales services, and expand the retirement care industry. Collaboration with stakeholders and better information dissemination are essential. The study concludes that a comprehensive industry roadmap is needed to position the Philippines as a leading retirement destination amidst evolving global trends and local challenges.
Keywords: 330; Retirement migration; Competitiveness; Retirement visa program; Retirement care industry